The Village Financial Management System: A Policy Towards Independent Villages - Puji Handayati; Mohd Rizal Palil (Jurnal Ekonomi dan Studi Pembangunan, 2020)
The ultimate focus of this research is to find out how to improve the capabilities of the Village Apparatus and the preparation of the Guidance Book for IT-based Village Finance Administration towards Good Village Governance. Then, this research also focuses on mentoring activities in 15 villages in Gempol sub-district. Assistance results in 15 villages in Gempol Subdistrict, Pasuruan Regency, show that village financial management software can be applied properly. Assistance results in 15 villages in Gempol Subdistrict, Pasuruan Regency, show that village financial management software can be applied properly. Although there are still some difficulties in implementation due to the lack of skills of the village apparatus due to age and parameter constraints that need to be adjusted. In general, the software still needs to be refined related to the filling and storage stages that are still considered inefficient. On the other hand, a tutorial guide book that has been tested from several aspects is considered very adequate. The usefulness of the village financial management guide book is very helpful for beginners in applying village financial management software.